2017
DOI: 10.3390/catal7050158
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dissolved Ions on the Water Purification Performance of TiO2-Impregnated Porous Silica Tubes

Abstract: TiO 2 -coated porous silica glass tubes containing macropores were fabricated and evaluated for their water-purification capacity using aqueous solutions of methylene blue. From the results of photocatalytic degradation tests at different initial methylene blue concentrations, the equilibrium adsorption constant (K) was determined to be 4.6 × 10 −2 L µmol −1 , and the Langmuir-Hinshelwood rate constant (k LH ) was calculated as 2.6 µM min −1 . To determine the influence of ions on the efficiency of methylene b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Figure 10 illustrates the difference between these two types of water when used for the decomposition of 20 µM of methylene blue solution. 24 The photocatalytic degradation of 20 µM of methylene blue in each solvent system was determined by measuring the absorbance at 663 nm, thereby corresponding to the adsorption peak of methylene blue. In these plots, treatment times of 0 min show the absorbance when the methylene blue solution reached its adsorption equilibrium before UV irradiation.…”
Section: Results Of Water Purification Testsmentioning
confidence: 99%
“…Figure 10 illustrates the difference between these two types of water when used for the decomposition of 20 µM of methylene blue solution. 24 The photocatalytic degradation of 20 µM of methylene blue in each solvent system was determined by measuring the absorbance at 663 nm, thereby corresponding to the adsorption peak of methylene blue. In these plots, treatment times of 0 min show the absorbance when the methylene blue solution reached its adsorption equilibrium before UV irradiation.…”
Section: Results Of Water Purification Testsmentioning
confidence: 99%
“…Truppi et al [15] conducted a comprehensive review of the recent progress in novel TiO 2 -based nanocomposites as visible-light-driven photocatalysts for versatile environmental applications. The mesoporous TiO 2 /SiO 2 composites from a biotemplating method (Yan et al [16]) and TiO 2 -impregnated porous silica tubes (Hayashi et al [17]) have been demonstrated as outstanding photocatalysts for dye purification under UV irradiation. Two/three-unit hybrid nanomaterials of MoS 2 /TiO 2 nanobelts (Liu et al [18]), three-dimensional WO 3 -TiO 2 nanoflowers (Lee et al [19]) and TiO 2 /RGO/Ag (Tian et al [20]) were constructed for photocatalytic Cr(VI) reduction, photo-oxidation of toxic aromatic volatile compounds, and photodegradation of methylene blue, respectively.…”
mentioning
confidence: 99%